Low-temperature solid-oxide fuel cells. (10th September 2014) - Wachsman, Eric; Ishihara, Tatsumi; Kilner, John
Abstract: Abstract : Solid-oxide fuel cells (SOFCs) are unique in their ability to directly convert the chemical energy of a wide variety of fuels to electric power with unmatched energy conversion efficiency. The articles in this issue of MRS Bulletin highlight the enormous potential of, and recent progress toward, operating SOFCs at lower temperatures (<650°C). Lower temperatures dramatically increase the number of potential applications for this technology as well as provide the opportunity to incorporate a wider variety of materials in SOFC power generation systems with greater reliability and lower cost. The articles in this issue describe materials development and processing for low-temperature SOFCs, including the enabling of nanotechnology and microelectromechanical systems-based cell designs, the development of highly active electrodes and their three-dimensional microstructural characterization, as well as the use of novel proton-conducting electrolytes, all of which provide new avenues of research. New fabrication methods are also being applied in the development of micro-SOFCs and microtubular SOFCs with higher power densities. Finally, advances in lowering performance degradation rates, a critical commercialization issue, are described.